SELF MANAGEMENT IN BUDDHIST PERSPECTIVE - Asep Priyono; Serli Permatasari; Nanda Sulistio Ardi; Saputro Edi Hartono (Yayasan Education and Social Center, 2023)
This research is motivated by the development of the times and advances in technology, to deal with these conditions, it is necessary to have good self-management. The purpose of this research is to find out how Self-Management in the Perspective of Buddhism. The research method used in this proposal is library research. The approach method in this scientific work uses text analysis and interpretation of the material text that will be used as a research source, namely in the form of primary sources and secondary sources. Primary sources consist of Buddhist scriptures, namely the Tripitaka, while secondary sources are taken from the opinions and writings of people who perceive self-management. Based on the literature review, it was found that self-management is very important to apply in everyday life. According to the teachings of Buddhism there are several suttas that discuss the importance of self-management, including namely; Dhammacakkappavattana Sutta, Parabhava Sutta, Cullaka Setthi Jataka, and Dhammapada Poem 103. As Buddhists, these suttas are our basis for implementing good self-management within ourselves